Determinant Analysis of Residual Net Income in The Sharia Cooperative: Company Size as Mediator - Bulan Karima Nurani; Hasan Mukhibad (Journal of Accounting and Strategic Finance, 2018)
This study aims to identify the effect of own capital and financing to net income (SHU), and how its effect when mediated by total assets. The population in this research are all Sharia Cooperative which operates in Semarang regency, there are 25 cooperatives. Sampling technique using is purposive sampling technique, which finally obtained 13 cooperatives with a period of observation 5 years. The method of analysis used to answer the hypothesis in this research is Path Analysis and Sobel Test. The results of this study indicate that partially own capital and financing have a significant positive effect on total asset, own capital has a significant positive effect on net income, financing has no significant effect on net income, total asset has an insignificant positive effect on net income, total asset did not succeed in mediating the effect of own capital on net income, and total asset succeed in mediating the effect of financing on net income.